Possible involvement of annexin A6 in preferential sperm penetration in the germinal disk region - Yoshinobu Ichikawa; Mei Matsuzaki; Shusei Mizushima; Tomohiro Sasanami (Bioscientifica, 2022)
During fertilization, avian sperm preferentially penetrate into the perivitelline membrane that covers the germinal disk region where the female nucleus is present. This phenomenon has been observed not only in domestic birds but also in wild birds; however, the mechanisms controlling sperm preference are still unclear. In this study, we investigated the possible involvement of annexin family protein in sperm-egg interaction in Japanese quail. Microscopic examination of fertilized eggs indicated that quail sperm penetration only occurred in the germinal disk region, and sperm localized outside the germinal disk were trapped in the perivitelline membrane. Western blot analysis and immunofluorescence microscopy revealed the presence of annexin A1 and A6 in the oocyte membrane, while annexin A6 localized in the perivitelline space of the germinal disk region. Further, our sperm binding assay using recombinant annexin A6 demonstrated that ejaculated sperm specifically bound to annexin A6 expressed in mammalian cell lines. These results suggest that annexin A6, which is expressed on the surface of oocytes, may function in sperm-egg interaction in the germinal disk region and that this binding may ensure sperm retention on the surface of the egg plasma membrane until fertilization takes place in Japanese quail.